Gelatine Extraction from Chicken Skin as Influenced by NaOH Pretreatment : doi: 10.5958/2581-6616.2021.00012.8 - Chand, Sagar; Mendiratta, S. K.; Kumar, Rajiv Ranjan; Talukder, Suman; C. K., Faslu Rehman; Madane, Pratap; Raypa , Pratima (Journal of Meat Science, 2022)
The present study was conducted to determine the effect of different NaOH concentrations for pretreatment of deserted chicken skins used thereof for gelatine extraction. The low temperature (50°C) treatment was used to extract maximum fat from minced skin and resulting skin was used to see the feasibility of gelatine extraction. The effect of NaOH pretreatment at different concentrations (0.1, 0.2 and 0.4%) on various quality attributes of chicken skin gelatine was observed. The proximate composition revealed moisture, protein, fat and ash content of chicken skin gelatine varying from 10.06 to 10.63%, 81.67 to 84.58%, 2.20 to 3.22% and 0.86 to 0.92%, respectively. The 0.4% NaOH showed highest protein, and lowest moisture, fat and ash content. The dried gelatine sheets were transparent and have mildly rancid odour; the yield varied from 4.27 to 4.81% and pH ranges from 4.89 to 4.93. A reduction in L* and a* value was observed with increasing NaOH concentration, but the percentage transmittance value was highest in 0.4% NaOH. The electrophoretic pattern showed discernible α-1 and α-2 chains with maximum distribution of proteins between 70 and 120kDa. Therefore, due to better quality attributes and maximum resemblance with control; 0.4% NaOH concentration is suggested for pretreatment of chicken skin during gelatine extraction.